Prototipe Smart Traffic Light (STL) berdasar Panjang Antrian menggunakan Internet of Things (IoT) - Jihan Athira Ramadhani; Agus Urip Ari Wibowo; Muhammad Diono (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
As an effort to regulate traffic, a Traffic Instruction Control Device (APIL) in the form of a Traffic Light is used. Traffic Lights are installed at various types of road intersections and crossing facilities. The function of traffic lights is very important so that traffic lights must be controlled as easily and efficiently as possible to facilitate traffic flow at a road intersection. However, after the use of Traffic Lights, there is still congestion due to the direction of vehicle arrivals from each lane not being simultaneous. This results in long queues in one of the Traffic Light lanes which makes the queue even longer due to the ineffectiveness of the red light duration of the existing Traffic Light. Therefore, researchers want to design a tool using 8 IR sensors as queue detection in each lane, then combining it with an automatic Traffic Light system can optimize the red and green lights according to the existing queue length. The results of the experiment found that in quiet conditions or no sensors detecting vehicles, the green light time is 20 seconds. When the condition of congestion 1 or the front IR sensor detects a vehicle, the green light time is increased by 5 seconds to 25 seconds. When traffic jam condition 2 or both IR sensors detect a vehicle, the green light is extended by 10 seconds to 30 seconds.